Alterations in transcriptome and proteome on metallothioneins following oxidative stress induced by sublethal doses of cadmium and gamma rays in Plantago ovata. (July 2013) - Ghoshal, Nirmalya; Talapatra, Shonima; Moulick, Amitava; Chakraborty, Anindita; Raychaudhuri, Sarmistha Sen
Abstract Purpose: To study the oxidative stress-induced changes by sublethal doses of cadmium chloride (CdCl2) and gamma irradiation, two redox-inducing agents, on metallothionein (MT) gene and protein expression in Plantago ovata Forsk (P. ovata). Materials and methods: Chlorophyll content was estimated to study the stress response in P. ovata seedlings following exposure to gamma irradiation and CdCl2. Lipid peroxidation and proline content, two oxidative stress markers, were also studied. The level of metallothionein gene and protein expression was further investigated using polymerase chain reaction (PCR), reverse transcription-PCR (RT-PCR), immunocytochemistry and flow cytometry. Results: Three MT genes of P. ovata namely PoMT 1, PoMT 2 and PoMT 3 were isolated, sequenced and characterized and their expressions were found to be altered in the case of both oxidative stresses in a dose-dependent and tissue-specific manner. The results were in agreement with the observations from immunocytochemistry and FACS analysis. Conclusions: The results suggest that both gamma irradiation and CdCl2 alter redox balance in P. ovata. The metallothionein gene may play an important role in metal tolerance and stress balance. It is conjectured that the stress-mediated imbalance is maintained by altered MT gene and protein expression.